Comparison of fungal and bacterial keratitis between tropical and subtropical Taiwan: a prospective cohort study - Chih-An Chen; Shiuh-Liang Hsu; Ching-Hsi Hsiao; David Hui-Kang Ma; Chi-Chin Sun; Hun-Ju Yu; Po-Chiung Fang; Ming-Tse Kuo (BMC, 2020)
Abstract Background Fungal keratitis (FK) has been shown to be a climate-sensitive disease. The differentiation between FK from bacterial keratitis (BK) was difficult. The purpose of this study was to compare the bacteriology and mycology between tropical and subtropical Taiwan and to investigate the independent risk factors for identification of fungi from bacteria. Methods Two hundred ninety-seven patients with clinical suspected microbial keratitis were prospectively enrolled. A fungal to bacteria rate (FBR), the number of fungi divided by bacteria identified, was determined to estimate the prevalence of fungi and bacteria. Clinical presentation, profiles of microorganisms, and predisposing risk factors were determined. Univariate and multivariate logistic regression analysis were used to investigate the independent risk factors. Results A total of 82 fungi and 143 bacteria were laboratory confirmed. The identification rate of fungus was higher in tropical Taiwan (p = 0.010). Among the fungi and bacteria confirmed, the FBR was 0.29 (22.4% vs. 77.6%) in subtropical Taiwan, and 0.70 (41.3% vs. 58.7%) in tropical Taiwan. Samples obtained in tropical area (p = 0.019), ocular trauma (p = 0.019), and plant exposure (p = 0.003) were independent risk factors for identification of fungus from bacteria. The predominant fungus isolated from corneal scraping were Fusarium solani (25%) and Trichosporon faecale (25%) in subtropical Taiwan; in tropical Taiwan was Fusarium spp. (50%). Conclusions The identification rate of fungus was higher in tropical Taiwan than subtropical Taiwan. Awareness of the local epidemiology is crucial for early diagnosis of fungal keratitis in tropical area.